The association between pelvic asymmetry and non-specific chronic low back pain as assessed by the global postural system - Qiuhua Yu; Huanjie Huang; Zhou Zhang; Xiaoqian Hu; Wenfeng Li; Le Li; Min Chen; Zhenwen Liang; Wai Leung Ambrose Lo; Chuhuai Wang (BMC Musculoskeletal Disorders, 2020)
Abstract Background Empirical evidence that demonstrates the relationship between pelvic asymmetry and non-specific chronic low back pain (NCLBP) is currently lacking. Objective To establish the reliability of the Global Postural System (GPS) in assessing pelvic asymmetry and identify the association between pelvic asymmetry parameters and the occurrence of NCLBP in young adults. Design A cross-sectional, regression study. Methods People who were aged between 18 and 30 and were diagnosed with NCLBP were recruited. Healthy individuals who were matched for age, sex, and education level were recruited as controls. Global Postural System (GPS) was employed to assess pelvic asymmetry. Prior to exploring the association, the reliability of GPS was assessed by the ICC (2, k) for interrater reliability, ICC (3, k) for intra-rater reliability, standard error and minimal detectable difference. Bivariate correlation analysis and logistic regression analysis were used to determine the relationship between pelvic asymmetry and the occurrence of NCLBP. Results Twenty-eight healthy participants and 28 people with NCLBP were recruited. Moderate to excellent ICCs were observed for the inter-rater and intra-rater reliability of most postural parameters. The bivariate correlation analysis indicated that age, body mass index and pelvic asymmetry parameters were related to the occurrence of NCLBP. Pelvic angle asymmetry (odds ratio = 1.17), and asymmetry of the distance between the posterior superior iliac spine and the floor (odds ratio = 1.21) were associated with NCLBP. Limitations This study did not explore the causal relationship between pelvic asymmetry in the sagittal plane/pelvic asymmetry in the transverse plane and the occurrence of NCLBP. The interpretation of the results may not be generalized beyond the sample population. Conclusions The GPS is a reliable method to assess pelvic asymmetry in a clinical setting. Two pelvic parameters were associated with the presence of NLBP. Measurement of pelvic asymmetry may assist in the early identification of potential occurrence of NCLBP but further work is required.